Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.